Reaction of Metals with Floor Cleaner Liquids - Siti Rahmah; Elsima Nainggolan; Aura F Harahap; Cut S Riska; Deri S Sitepu; Anna C ASiregar; Aria Nanda; Debora P Simanjuntak (Universitas Negeri Medan, 2020)
Metals react with acid to produce hydrogen gas. Some of floor cleaner liquids contain concentrated strong acid such as HCl. This study was conducted to react metals (Zn, Al, Fe, Cu) with floor cleaner liquids (WPC and Vixal) that contain 17% HCl to produce hydrogen gas. The most hydrogen gases were resulted from reaction between Al and both of floor cleaner liquids. They show the same trend Al lebih besar dari Cu lebih besar dari Zn lebih besar dari Fe for the volume of hydrogen gas produced . It was not appropriate with theory due to different of surface area of each metals used.